Design of interactive learning courseware for data structures - Ang, Stella (2018)
The digital revolution has brought huge changes in how we access, share and consume information today. The Internet is a good example of how our lives have been made easier and more convenient. Not only does it allow for communication, it provides a platform to study and learn. When compared to traditional learning, there is a clear evidence that online learning (or e-Learning) brings a better experience. The flexibility of e-Learning allows learners to set their own pace and access course materials at their own convenience.